Principles in the Diagnosis of Early Manifestations of Acute Lung Lesion - V. V. Moroz; A. M. Golubev (Общая реаниматология)
The editorial assesses the diagnostic criteria for acute lung lesion (ALL), which are based on its clinical manifestations, oxygenation index, X-ray signs, and pulmonary wedge pressure. The clinical experience suggests that the majority of the above signs do not reflect the early stages of acute lung lesion. The authors propose to use additional diagnostic tests, such as determination of pulmonary extravascular water, pulmonary capillary permeability index, identification of systemic inflammatory response markers, and information on which can be provided by up-to-date technologies. It is necessary to detect early signs of acute lung lesion to perform appropriate therapy for the prevention of subsequent complications.